Optimization of the Fc-fusion protein refolding method produced from the bacterial expression system - P. S. Astrelina; S. A. Ishchuk; A. V. Kabanova; R. V. Drai (Разработка и регистрация лекарственных средств)
Introduction. The production of Fc-fused proteins in prokaryotic systems often results in the formation of insoluble aggregates due to improper folding of polypeptide chains. To obtain functional proteins, a refolding step is required. However, developing refolding parameters can be time-consuming. The optimization of renaturation conditions using the Design of Experiments (DoE) approach allows for the calculation of optimal process parameters and the evaluation of contributing factors and their interactions.Aim. This study aims to evaluate the effects of denaturation buffer pH, as well as oxidative and reducing agent concentrations, on the efficiency of Fc-fusion protein refolding in vitro and to determine optimal refolding parameters.Materials and methods. Fc-fusion protein inclusion bodies were obtained from an Escherichia coli BL21 bacterial expression system. The experiment was designed using an orthogonal composite design (Orthogonal Central Composite Design, CCO). Experimental design, statistical data processing, and parameter optimization were conducted using MODDE (v. 12.1, Sartorius Stedim Data Analytics AB, Germany). Chromatographic purity and yield of the target protein, as determined by high-performance size-exclusion chromatography, were used as response variables.Results and discussion. The DoE approach successfully optimized the Fc-fusion protein refolding process. Response surface plots were constructed, and the optimal factor values were determined. The statistical models demonstrated high predictive accuracy and data reproducibility. The refolding process was successfully validated under optimized conditions, resulting in a decrease in high-molecular-weight impurities and improperly folded protein forms. The chromatographic purity of the target protein increased by more than 10 %, as confirmed by high-performance size-exclusion chromatography.Conclusion. The study established significant effects of buffer pH, redox pair concentrations, and their interactions on the yield and chromatographic purity of the Fc-fused protein. The interplay between oxidative and reducing components and buffer pH was demonstrated. Increasing the buffer pH led to improved refolding efficiency.